MSMEs’ Strategy for Delivering Messages through TikTok Content - M. Rifqi Fauzan Adyatma (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2022)
Competition between large companies and small businesses such as Micro, Small, and Medium Enterprises (MSMEs) is unavoidable. Quoting from previous research, MSME actors lack knowledge, funding, and time which may hamper their marketing communications. Content marketing through TikTok is now an option. The purpose of this study was to determine the model of the message delivery strategy through TikTok carried out by MSME actors referring to the theory of new media and content creation elements. This research uses a qualitative approach with a case study method. Data collection was carried out by interviewing eight MSME actors who use TikTok as a means of marketing communication. The results show that the target market is Generation Z, the content presented focuses on trends, the communication style is carried out by indirect marketing with diverse content schedules, and customer engagement through comments is very important.